2007
DOI: 10.1007/s11661-007-9160-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Carbon and Retained Austenite Distributions in Martensitic Medium Carbon, High Silicon Steel

Abstract: The retained austenite content and carbon distribution in martensite were determined as a function of cooling rate and temper temperature in steel that contained 1.31 at. pct C, 3.2 at. pct Si, and 3.2 at. pct noniron metallic elements. Mo¨ssbauer spectroscopy, transmission electron microscopy (TEM), transmission synchrotron X-ray diffraction (XRD), and atom probe tomography were used for the microstructural analyses. The retained austenite content was an inverse, linear function of cooling rate between 25 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 50 publications
6
28
0
1
Order By: Relevance
“…C is also enriched at the martensite plate boundary with a content of 6e7 at% as indicated by the arrows and the dashed line in Fig. 8 (a), agreeing with the saturation carbon content of Cottrell atmospheres [37,38]. Fig.…”
Section: Apt Results and Discussionsupporting
confidence: 76%
“…C is also enriched at the martensite plate boundary with a content of 6e7 at% as indicated by the arrows and the dashed line in Fig. 8 (a), agreeing with the saturation carbon content of Cottrell atmospheres [37,38]. Fig.…”
Section: Apt Results and Discussionsupporting
confidence: 76%
“…The films of retained austenite shown in Fig. 2 are on the order of 10 nm in thickness, consistent with previous research [33].…”
Section: Microstructural Featuressupporting
confidence: 90%
“…Previous transmission electron microscope studies of lath martensite have shown that the austenite-to-martensite phase transformation typically does not go to completion, and as a result, some of the parent austenite phase is retained as interlath films at room temperature [30][31][32][33]. In the present system, retained austenite was identified; however, it seemed to be present in a rather low quantity, estimated at a few volume percent.…”
Section: Microstructural Featuresmentioning
confidence: 59%
“…Similar behaviors were already reported in low to medium carbon steels [1,15,16]. As already observed previously, during the present experiments with 100Cr6 samples, the measured lattice parameters of retained austenite during quenching show a non-linear change of the slope (continuous decrease) below Ms (Fig.…”
supporting
confidence: 91%